Manual of sheep diseases. - Hindson, J.C.; Winter, Agnes C. (Oxford, United Kingdom Blackwell Science, 2002)
"This revised and updated version of Outline of Clinical Diagnosis in Sheep now covers the whole field of diagnosis, treatment and prevention of diseases and poor production of sheep. It is aimed a the non-specialists veterinarian and fills a niche between the large, comprehensive books on sheep and the shorter texts aimed at farmers. It will also appeal to all those involved in sheep production, and is a valuable reference for veterinary students. A wide range of diseases and conditions is covered, together with important aspects of production such as lamb output and growth rates. New sections have been added on nutrition (which has a significant effect on all aspects of production), anaesthesia, vaccination programmes, and parasite control"--
Contents; 1: Introduction; 2: Suboptimal reproductive performance (SORP); 3: Abortion; 4: Dystocia and vagino-cervical prolapse; 5: Male infertility; 6: Periparturient ewe losses; 7: Mastitis, udder and teat lesions; 8: Perinatal lamb losses; 9: Inadequate growth rate; 10: Diarrhoea; 11: Tenesmus; 12: Adult weight loss; 13: Mouth disorders; 14: Lameness; 15: Changed behaviour and neurological dysfunction; 16: Eye disorders/visual defects; 17: Anaemia; 18: Jaundice; 19: Abdominal distension and abdominal pain; 20: Wool loss and skin lesions; 21: Respiratory disease; 22: Found dead and sudden death; Index
UP System perpetual contents
Revised edition of: Outline of clinical diagnosis in sheep / J.C. Hindson, Agnes C. Winter, 1990
Includes bibliographical references (page 282)
Keywords: Sheep -- Diseases -- Diagnosis